2014
DOI: 10.17784/mtprehabjournal.2014.12.202
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a single session of transcranial direct current stimulation combined with virtual reality training on functional mobility in children with cerebral palsy: A randomized, controlled, double-blind trial.

Abstract: Introduction:Abnormal postural control in children with cerebral palsy (CP) exerts a negative impact on activities of daily living. The Timed UpandGo (TUG) test is a valid, reliable test for the evaluation of functional mobility in children with CP. Objective:The aim of the present study was to determine the effects of a single session of transcranial direct current stimulation (tDCS) over the primary motor cortex combined with mobility training using a virtual reality system on functional mobility in children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 15 publications
(19 reference statements)
0
14
0
Order By: Relevance
“…The article mainly studies: Stroke rehabilitation (i) [ 25 ] [ 30 ] The effects of NIBS, VR and its combination on therapy for upper limb training in patients with subacute stroke. The effects of combining NIBS with VR-based motor skill training in patients with subacute stroke (ii) [ 31 ] The effect of adding NIBS to VR therapy, for upper limb training in unilateral stroke [ 29 ] Whether combining NIBS with VR training could improve upper limb function in subacute stroke patients [ 28 ] The effects of adding NIBS to a VR-BCI therapy for motor recovery after stroke [ 32 ] The effects of adding NIBS in VR therapy to improve upper limb motor function after stroke (iii) [ 33 ] The effects of NIBS-VR paradigm for upper limb rehabilitation in a stroke survivor with severe hemiparesis Phobia and PTSD (ii) [ 34 ] [ 35 ] The effects on acute anxiety of adding NIBS to a VR experience for patients with spider phobia The impact on emotion regulation of adding NIBS to a VR experience for patients with spider phobia [ 36 ] The use of NIBS during VR experience to reduce psychophysiological arousal and symptoms in veterans with PTSD Cerebral palsy (ii) [ 37 ] The effects of a single session of NIBS combined with VR training on functional mobility in children with cerebral palsy [ 26 ] The effects of a single session of NIBS combined with VR training on the balance of children with cerebral palsy [ 38 ] ...…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The article mainly studies: Stroke rehabilitation (i) [ 25 ] [ 30 ] The effects of NIBS, VR and its combination on therapy for upper limb training in patients with subacute stroke. The effects of combining NIBS with VR-based motor skill training in patients with subacute stroke (ii) [ 31 ] The effect of adding NIBS to VR therapy, for upper limb training in unilateral stroke [ 29 ] Whether combining NIBS with VR training could improve upper limb function in subacute stroke patients [ 28 ] The effects of adding NIBS to a VR-BCI therapy for motor recovery after stroke [ 32 ] The effects of adding NIBS in VR therapy to improve upper limb motor function after stroke (iii) [ 33 ] The effects of NIBS-VR paradigm for upper limb rehabilitation in a stroke survivor with severe hemiparesis Phobia and PTSD (ii) [ 34 ] [ 35 ] The effects on acute anxiety of adding NIBS to a VR experience for patients with spider phobia The impact on emotion regulation of adding NIBS to a VR experience for patients with spider phobia [ 36 ] The use of NIBS during VR experience to reduce psychophysiological arousal and symptoms in veterans with PTSD Cerebral palsy (ii) [ 37 ] The effects of a single session of NIBS combined with VR training on functional mobility in children with cerebral palsy [ 26 ] The effects of a single session of NIBS combined with VR training on the balance of children with cerebral palsy [ 38 ] ...…”
Section: Resultsmentioning
confidence: 99%
“…The reviewed studies reported different blinding approaches to prevent both participant and/or experimenter biases [ 44 ]. Six studies, [ 26 , 29 , 31 , 37 39 ], reported double blinding (patients and therapists); single blinding on the patient side was reported in seven studies [ 28 , 30 , 32 , 34 36 , 41 ]; and the remaining three studies reported single blinding only in the therapist side.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations